PENGEMBANGAN KOMIK DIGITAL â€œLETâ€™S LEARN ABOUT VIRUSâ€ SEBAGAI MEDIA PEMBELAJARAN BIOLOGI SISWA KELAS X SMA - Irfana, Naily; Iswari, Retno Sri; H.B, F. Putut Martin (Journal of Biology Education, 2017)
This study aimed to test feasibiity of digital comic Let?s Learn about virus as learning media in increase comprehension 10th grade of Senior High School students about virus. The study design is Research and Development (R&D). Small scale and wide scale test and trials held at SMA Negeri 11 Semarang on class X MIPA 6 in odd semester of 2016/2017 academic year. Samples taken in random sampling and design research with One Group Pretest and Posttest Design. The results of the validation indicates that the digital comics very decent used in learning with a percentage of the media expert 92%, material expert 89%,  and biology teacher 96%. Small scale trial results stated that 92% of students agreed the learning virus? material using digital comic?s media. The effectiveness of digital comics seen from wide scale trial results. The results obtained from wide scale trial is the average value of N-Gain in the amount 0.68 category medium and thoroughly classical students achieve 88.9% with the results of the assessment of attitudes and skills the average is very good. Teachers and students give positive response toward the use of digital comics.